Experimental malaria: Contamination of malalaria strain and experimental animals by eperythrozoon coccoides - Andrade Jr., Heitor Franco de; Laurenti, Márcia Dalastra; Goto, Hiro; Duarte, Maria Irma Seixas; Corbett, Carlos Eduardo Pereira (Revista do Instituto de Medicina Tropical de São Paulo, 1986)
This report describes an accidental contamination of a murine malaria strain (Plasmodium berghei) by a hemoparasite (Eperythrozoon coccoides) wich resulted in important modification of the experimental malarial infection behaviour. The hemoparasite "was detected by optical and electron microscopy, and the contamination was attributed to rodents usually employed in the strain maintenance, obtained from the same colony. Control measures available for this type of accidental infections are discussed and proposed the use of parenteral tetracyclines in breeding animals using the untreated Fl animals, for experimentation. The importance of this contamination is discussed in some detail.